THE INFLUENCING OF MEDIA SENTENCE BUILDING GRID TO THE INCREASING WRITING ABILITY ON MIDWIFERY COLLEGERS AT STIK BINA HUSADA PALEMBANG - Pamuji, Arief (JURNAL DIDASCEIN BAHASA, 2018)
ABSTRACT : The objective of this research was to find out whether or not thereis a influencing of media sentence building grid to the increasing writing ability on midwifery students. This research was descriptive study and the sample of this research was taken by using total sampling with total 70 midwifery students at STIK Bina Husada Palembang. The data were obtained by using writing test that were analyzed by using t-test and paired sample correlation analyses by means of Statistical Product and Service Solution (SPSS) version 12.00 computer program. Based on the data analysis, the influencing  of media sentence building to the increasing writing ability in paragraph was 4.750 at the significance level p< 0.05 in two tailed. Since the value of t-obtained was higher than the critical value of t-table and the paired sample was 0.540. Most of students got the improvement and the outstanding level after giving the treatment. It meant that there was a significant influencing of building sentence grid to the increasing writing ability. Keywords: influencing, media sentence building grid, and writing ability.